Lupus anticoagulant associated with low grade B-cell lymphoma and IgM paraproteinaemia with lupus cofactor phenomenon on DRVVT and SCT assays - a possible novel association - Ting Hon Stanford Li; Pui Lun Yip; Hui Yiu Chan; Ho Kin Stephen Chan; Wai Shan Wong (Thrombosis Journal)
Abstract Background Lupus anticoagulant (LA) is an in vitro phenomenon with prolongation of a phospholipid-dependent coagulation test which is not due to an inhibitor specific to a coagulation factor. Occasionally, addition of normal pooled plasma to patient plasma with lupus anticoagulant potentiates the inhibitory effect of lupus anticoagulant in the mixture, resulting in a paradoxical prolongation instead of shortening of clotting time. The phenomenon has been termed the “lupus cofactor effect”. Lupus anticoagulant are known to be associated with lymphoma and immunoglobulin M (IgM) paraproteinaemia. Cases of lymphoplasmacytic lymphoma with concomitant IgM paraproteinaemia and lupus anticoagulant demonstrating lupus cofactor phenomenon on activated partial thromboplastin time (APTT) assay has been reported previously. However, to our best knowledge, there were no reported cases of low grade B-cell lymphoma with positive LA results and lupus cofactor effect demonstrated on dilute Russell’s viper venom time (DRVVT) and/or silica clotting time (SCT) assays in the literature. Case presentation We report two cases of low grade B-cell lymphoma associated with monoclonal IgM paraprotein, high levels of anti-cardiolipin IgM antibody and presence of lupus anticoagulant with lupus cofactor phenomenon on DRVVT and/or SCT assay. Conclusions Our cases demonstrate a possible novel association between low grade B-cell lymphoma, IgM paraproteinaemia, high levels of anti-cardiolipin IgM antibody and the presence of lupus cofactor effect on DRVVT and SCT assays. The DRVVT assay in the first patient and SCT assay in second patient were falsely negative in the neat sample or less diluted sample, and the lupus anticoagulant activities were only revealed on dilution of samples with normal pooled plasma. This highlights the potential importance of dilution of samples with normal pooled plasma while evaluating the LA status of low grade B-cell lymphoma patients with a markedly prolonged APTT and/or prolonged PT by DRVVT and SCT assays, especially if there is concomitant IgM paraproteinaemia and a high level of anti-cardiolipin IgM antibody.